Role of 3D-CISS sequence in differentiating cerebellopontine meningiomas from schwannomas. - Mourão, RS; Ventura, N; Corrêa, DG (Neuroradiology Journal, 2026)
Purpose: Differentiating cerebellopontine meningioma (CPM) from schwannoma (CPS) can be challenging. In this location, schwannomas alter the composition of the perilymphatic fluid differently from meningiomas, which has repercussions on magnetic resonance imaging. This study aims to distinguish between these tumors based on the labyrinthine fluid signal on 3D-CISS. Methods: Patients with histologically confirmed CPM and CPS were selected. Analyses were performed considering visual signal intensity from the vestibule and cochlea, and the signal ratios between the vestibules (aV/uV) and the cochleae (aC/uC) on affected and unaffected sides. The signal intensity ratio between vestibule and cerebellum (aV/aCH), vestibule and cerebrospinal fluid (aV/aCSF), and cochlea and cerebrospinal fluid (aC/aCSF), on affected sides, as well as the vestibule and cerebellum ratio between affected and unaffected sides ([aV/aCH]: [uV/uCH]), were also compared. Results: Statistically significant differences were demonstrated for visual signal reduction (p <.001) and for aV/uV (p =.005), aC/uC (p <.001), [aV/aCH]: [uV/uCH] (p =.018), aV/aCSF (p =.036), and aC/aCSF (p =.001) ratios, with lower values associated with schwannomas. The aC/aCSF ratio showed the highest accuracy (84.2%), with a cutoff value of 0.63, and the second-largest area under the Receiver Operating Characteristic (ROC) curve (0.791). The visual reduction of cochlear signal showed the second-highest accuracy (83%). The aC/uC ratio demonstrated the largest area under the ROC curve (0.857) and the third-highest accuracy (75.5%), using 0.74 as the cutoff value. Conclusion: The visual reduction of cochlear signal and the aC/uC and aC/aCSF ratios proved to be the most effective parameters for distinguishing CPM from CPS when the labyrinthine fluid is utilized.